Development of a core descriptor set for Crohn's anal fistula. (22nd December 2022) - ,
Abstract: Aim: Crohn's anal fistula (CAF) is a complex condition, with no agreement on which patient characteristics should be routinely reported in studies. The aim of this study was to develop a core descriptor set of key patient characteristics for reporting in all CAF research. Method: Candidate descriptors were generated from published literature and stakeholder suggestions. Colorectal surgeons, gastroenterologists and specialist nurses in inflammatory bowel disease took part in three rounds of an international modified Delphi process using nine‐point Likert scales to rank the importance of descriptors. Feedback was provided between rounds to allow refinement of the next ratings. Patterns in descriptor voting were assessed using principal component analysis (PCA). Resulting PCA groups were used to organize items in rounds two and three. Consensus descriptors were submitted to a patient panel for feedback. Items meeting predetermined thresholds were included in the final set and ratified at the consensus meeting. Results: One hundred and thirty three respondents from 22 countries completed round one, of whom 67.0% completed round three. Ninety seven descriptors were rated across three rounds in 11 PCA‐based groups. Forty descriptors were shortlisted. The consensus meeting ratified a core descriptor set of 37 descriptors within six domains: fistula anatomy, current disease activity and phenotype, risk factors, medical interventions for CAF, surgical interventions for CAF, and patient symptoms and impact on quality of life. Conclusion: The core descriptor set proposed for all future CAF research reflects characteristics important to gastroenterologists and surgeons. This might aid transparent reporting in future studies.